2009
DOI: 10.1016/j.jvs.2009.08.062
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat model of abdominal aortic aneurysm using a combination of intraluminal elastase infusion and extraluminal calcium chloride exposure

Abstract: Objective: An ideal animal model of abdominal aortic aneurysm (AAA) is of great importance for clarifying unknown complex mechanisms of the pathogenesis. We introduce a new, simple technique to create reliable AAAs that simulate human aneurysms. Methods: Experimental models of AAAs were created in 71 rats by means of a 20-minute application of intraluminal elastase (30 U) and extraluminal calcium chloride (0.5M) in the 1-cm segment of infrarenal abdominal aorta (group EC, n ‫؍‬ 26). A single application of ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 32 publications
4
70
0
Order By: Relevance
“…12 Because we regarded this AAA condition as simulating the pre-existing form or a small AAA in humans, edaravone was given beginning 7 days after aneurysm preparation. The present study showed that edaravone treatment starting at 7 days after aneurysm preparation inhibited AAA further development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Because we regarded this AAA condition as simulating the pre-existing form or a small AAA in humans, edaravone was given beginning 7 days after aneurysm preparation. The present study showed that edaravone treatment starting at 7 days after aneurysm preparation inhibited AAA further development.…”
Section: Discussionmentioning
confidence: 99%
“…However, we demonstrated that our AAA model is simple and easy to perform, is highly reliable, and is reproducible to create a saccular aneurysm. 12 The second limitation is the lack of protein analysis for proinflammatory cytokines and MMPs and signal transduction mechanism analysis for the antioxidative effects of edaravone. The most likely mechanism for the protective effect of edaravone is a reduction in oxygen radicals, but further studies are needed, especially with regard to its effects on inflammatory cell infiltration and to exclude other possible mechanisms of AAA regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental AAA model was created by means of a simple application of both intramural elastase and extraluminal calcium chloride, according to our recently described method. 21 Briefly, rats anesthetized with an intra-peritoneal administration of pentobarbiturate (1 mg/kg) were placed under an operating microscope Leica M651 (Leica Microsystems, Heerbrugg, Switzerland) with 6 to 10 times magnification. After a midline abdominal incision and an abdominal aorta exposure, 30 U of elastase (135 U/mg; Elastin Products, Owensville, Mo) was applied to the 1 cm infrarenal aorta intraluminally and 0.5 M of CaCl 2 (Sigma-Aldrich, Tokyo, Japan) extraluminally for 20 minutes.…”
Section: Ratsmentioning
confidence: 99%
“…The AAA is defined as when the dilation ratio is more than 50%. 21 Quantitative real-time polymerase chain reaction (PCR) analysis. Total RNA was isolated from AAA samples using an RNeasy fibrous tissue mini-kit (Qiagen K.K., Tokyo, Japan) according to manufacturer's instructions.…”
Section: Ratsmentioning
confidence: 99%